Optimization of spray drying for lulo (Solanum quitoense Lam.) pulp using response surface methodology - Arango-Bedoya, Oscar; Rojas-Inagan, Roberth; Martínez-Suarez, Hernan; Hurtado-Benavides, Andrés (Revista de Ciencias Agrícolas, 2024)
Lulo (Solanum quitoense Lam.) is an exotic fruit with high potential in international markets due to its intense aromatic characteristics and its content of nutritional and bioactive compounds. However, it is highly perishable, which backslashes its potential for international exportation. Despite the drying processes affect the nutritional and sensory characteristics, fruit powders obtained by spray drying are promising products for the food, cosmetic, and pharmaceutical industries. This work was conducted aiming to optimize the spray-drying process of lulo pulp. A Box-Behnken design with response surface methodology was used, in which the factors evaluated were inlet air temperature (160 - 220 °C), maltodextrin concentration (15-35%), and whey protein concentration (WPC) (1-5% w/w). The feed rate and air velocity were kept constant at 4 mL/min and 9 m/s, respectively. The optimization resulted in an inlet air temperature of 205.6 °C, 35% maltodextrin, and 1.96% WPC. Under these conditions, the mathematical model estimated a powder yield of 62.8%, a moisture content of 2.3 %, a bulk density of 0.49 g/mL, a solubility of 91.9 %, and an ascorbic acid content of 120.8 mg/100 g powder. The optimal process conditions and the mixture of encapsulants (MD and WPC) allow for obtaining lulo powder with adequate yield and quality characteristics.